Plutarco en The True Intellectual System of the Universe - Strok, Natalia (2018)
“Plutarch in ‘The True Intellectual System of the Universe’”. In The True Intellectual System of the Universe Ralph Cudworth uses a great deal of sources in order to reconstruct past doctrines. In this paper, I propose that we pay attention to the way he uses Plutarch of Chaeronea’s work. The hypothesis that guides this article sustains that Cudworth uses this work as a source of ancient thought despite not totally agreeing with his interpretation of Plato. This means that Plutarch’s work has two levels of reading: on the one hand, its exposition as a source of other authors; and, on the other hand, the interpretation that Plutarch himself makes of his sources, especially, of Plato. This will allow me to draw some conclusions concerning Cudworth’s work as a historian of philosophy and his relationship with Platonic philosophy.